Hemodynamic effects of sacubitril/valsartan in patients with reduced left ventricular ejection fraction over 24 months: a retrospective study - Abumayyaleh, Mohammad S. A.; Demmer, Jonathan; Krack, Carina; Pilsinger, Christina; El-Battrawy, Ibrahim; Behnes, Michael; Aweimer, Assem; Mügge, Andreas; Lang, Siegfried; Akın, Ibrahim (American journal of cardiovascular drugs, 2022)
The effects of sacubitril/valsartan in patients with chronic heart failure with reduced ejection fraction (HFrEF) were recently reported. However, the hemodynamic impact of this well-established treatment in patients with HFrEF has been poorly systematically researched.